Distortion-induced interfacial charge transfer at single cobalt atom secured on ordered intermetallic surface enhances pure oxygen production - Mondal, Soumi; Riyaz, Mohd; Bagchi, Debabrata; Dutta, Nilutpal; Singh, Ashutosh Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (ACS Nano, 2023)
In this work, atomic cobalt (Co) incorporation into the Pd2Ge intermetallic lattice facilitates operando generation of a thin layer of CoO over Co-substituted Pd2Ge, with Co in the CoO surface layer functioning as single metal sites. Hence the catalyst has been titled Co-1-CoO-Pd2Ge. High-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy confirm the existence of CoO, with some of the Co bonded to Ge by substitution of Pd sites in the Pd2Ge lattice. The role of the CoO layer in the oxygen evolution reaction (OER) has been verified by its selective removal using argon sputtering and conducting the OER on the etched catalyst. In situ X-ray absorption near-edge structure and extended X-ray absorption fine structure spectroscopy demonstrate that CoO gets transformed to CoOOH (Co3+) in operando condition with faster charge transfer through Pd atoms in the core Pd2Ge lattice. In situ Raman spectroscopy depicts the emergence of a CoOOH phase on applying potential and shows that the phase is stable with increasing potential and time without getting converted to CoO2. Density functional theory calculations indicate that the Pd2Ge lattice induces distortion in the CoO phase and generates unpaired spins in a nonmagnetic CoOOH system resulting in an increase in the OER activity and durability. The existence of spin density even after electrocatalysis is verified from electron paramagnetic resonance spectroscopy. We have thus successfully synthesized intermetallic supported CoO during synthesis and rigorously verified the role played by an intermetallic Pd2Ge core in enhancing charge transfer, generating spin density, improving electrochemical durability, and imparting mechanical stability to a thin CoOOH overlayer. Differential electrochemical mass spectrometry has been explored to visualize the instantaneous generation of oxygen gas during the onset of the reaction.
Keywords: DEMS; interfacial charge transfer; Intermetallic; long-termstability; operando spectroscopic techniques; Oxygen Evolution Reaction; structuraldistortion

Dopant and exfoliation induced simultaneous modification of charge density and C―C coupling sites for efficient CO2 photoreduction to ethylene - Das, Kousik; Chakraborty, Subhajit; Kediya, Siddhi; Singh, Ashutosh Kumar; Das, Risov; Mondal, Soumi; Riyaz, Mohd; Goud, Devender; Dutta, Nilutpal; Vinod, Chathakudath P.; Peter, Sebastian C. (Angewandte Chemie-International Edition, 2025)
The photochemical conversion of CO2 into C2+ products has emerged as an attractive method for synthesizing valuable chemicals and fuels using abundant solar energy. However, the challenge lies in enhancing the efficiency and selectivity of C2+ product formation. In this study, we employed a heteroatom doping strategy to optimize the photocatalytic parameters and achieve excellent efficiency and selectivity in the photocatalytic CO2 reduction to C2+ product formation. Our experimental analysis revealed that the local electronic structure of the catalyst, modified by In-doping, enables enhanced efficiency. Additionally, the incorporation of Cu facilitates the coupling of C1 intermediates, resulting in excellent selectivity towards C2+ products. The CO2 reduction performance is further enhanced through exfoliation, which increases the exposure of active sites and extends the charge carrier lifetime by reducing the charge diffusion length. We report that the rate of formation of C2H4 reached 54.3 mu molh(-1)g(-1) with an outstanding selectivity of 91% over the exfoliated CuIn-doped AgBiP2S6 catalyst. By elucidating the role of heteroatom doping and exfoliation in enhancing both the efficiency and selectivity of C2+ product formation, our study contributes to advancing the development of sustainable and efficient photocatalytic CO2 conversion technologies.
Keywords: C & horbar; C coupling; CO2 reduction; Doping; Exfoliation; Photocatalysis